Potencial de Moringa oleifera L. na fitorremediação de águas contaminadas pelo herbicida atrazina - Sousa, Halisson Araújo de (2018)
Phytoremediation is an emerging, low-cost technique that uses plants to remove, transform or stabilize contaminants in soil, air, and water. Some plants identified as good candidates for soil and water remediation have been evaluated for the biochemical and genetic processes involved in capturing, transporting and storing the pollutants. Moringa oleifera presents some of the important characteristics in the selection of phytoremediate plant species. Among them are its coagulant / flocculant properties, good adaptability to the climatic conditions of Ceará, fast growth rate and great resistance to pests. Thus, the present work had as objective to evaluate the phytoremediation potential of this species in water contaminated by atrazine, a widely used herbicide. For this, plants of M. oleifera, using a hydroponic cultivation, were put in contact with waters artificially contaminated with atrazine, in the concentrations of 2.0, 1.0, 0.2 and 0.05 mg.L-1 in periods of 10, 20 and 30 days. Phytoremediation potential was evaluated through plant growth parameters, enzymatic activities and the ability to decrease the concentration of atrazine in water. The dosage of enzymes related to oxidative stress showed that leaves and roots of atrazine treated plants had a distinct expression profile of these molecules. In general, significant increases in peroxidase (POX) were observed, mainly in roots of plants submitted to atrazine treatment, and other enzymes such as ascorbate peroxidase (APX), catalase (CAT). The evaluation of the levels of atrazine in the hydroponic medium showed that with 10 days of treatment, the moringa plants managed to reduce atrazine contents by 96.0 %. After 30 days of treatment, the removal rate was 87.15 %. The results indicate that M. oleifera it is a specie that has great potential for the phytoremediation of environments contaminated with atrazine and /or other compounds of environmental interest.